2007
DOI: 10.1080/10942910601113319
|View full text |Cite
|
Sign up to set email alerts
|

Antiulcer Potential of a Standardized Extract of Red Orange Juice in the Rat

Abstract: A standardized red orange extract (Red Orange Complex, ROC) has been evaluated for its potential protective effect on ethanol-and indomethacin-induced gastric lesions in rats. Oral administration of the ROC significantly prevented the development of gastric lesions in these experimental models. In addition, the effect of the ROC on the spontaneous healing of acetylsalicylic acid (ASA) ulcers in rats was examined. The spontaneous healing of gastric ulcer was significantly accelerated by repeated administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…[26] McCarty [27] reported that the peroxynitrite-scavenging ability of plant phenolic compounds, especially flavonoids, is important to the cardioprotective effects associated with high fruit and vegetable intakes. Although citrus fruit juice contains a variety of nutrients and phytochemicals and has numerous healthy benefits, [28,29] the exploitable functional components in citrus fruit peels could not be ignored. Citrus fruit peels have abundant phenolics content and polymethoxyflavones content, which are responsible for the peroxynitrite-scavenging activities of citrus fruit peels.…”
Section: Discussionmentioning
confidence: 98%
“…[26] McCarty [27] reported that the peroxynitrite-scavenging ability of plant phenolic compounds, especially flavonoids, is important to the cardioprotective effects associated with high fruit and vegetable intakes. Although citrus fruit juice contains a variety of nutrients and phytochemicals and has numerous healthy benefits, [28,29] the exploitable functional components in citrus fruit peels could not be ignored. Citrus fruit peels have abundant phenolics content and polymethoxyflavones content, which are responsible for the peroxynitrite-scavenging activities of citrus fruit peels.…”
Section: Discussionmentioning
confidence: 98%